Coca, coffee and cacao: Drug control policy and life strategies in farmers of the Monzón Valley - Grillo, Luciana (2018)
The objective of this research is to analyze how the implementation of state initiatives in drug control policy is related to the configuration of life strategies in farmers of the Monzón Valley. To do this, it (a) identifies how the implementation process was developed in drug control policies; (b) characterizes the narratives and practices constructed by farmers based on the application of these initiatives; and (c) analyzes how the interrelation between the implementation process and the capitals of the population is linked to the configuration of life strategies. The study, qualitative and exploratory, finds that the consequences of state initiatives in the social groups of the valley varies because of factors such as origin, age, gender, previous agricultural experience and location of the plots, which are expressed as capitals that facilitate or restrict the decisions of rural actors. From them, farmers will deploy different life strategies, which can be observed as practices and narratives developed to adapt and give meaning to the process they now live.